Emergency Department: an untapped opportunity #SmokeFreeMY - Nurumal, Mohd. Said (Malaysian Integrated Medical Professionals Association (MIMPA), 2014)
In managing shortness of breath due to asthma or related symptoms, the practice in the emergency department is often uniform across the country. Patients who attend unannounced, ‘walk-in’ is the medical lingo, with symptoms suggestive of a sudden asthma attack will be directed to the asthma bays for immediate treatment. These patients are often nebulised after being assessed and diagnosed with acute asthma. However, these so called ‘frequent flyers’ of asthma bays did not only consist of acute asthma patients but also breathing difficulties mimicking asthma as a result of smoking. A systematic review study on management of smoking-related illness at an emergency department reveals more than 25 million smokers are present yearly. Therefore, a large number of cases seen in the emergency department were smoking induced.